Demokrasi Sosial menurut Herbert Marcuse - CB. Mulyatno (Arete, 2013)
Herbert Marcuse lives in an era marked by terrible human tragedies. He has been experiencing the first and second world wars and the atrocities of Nazism under Hitler’s regime. In that situation, he is compelled to reflect on the meaning of democracy, freedom and justice. In a broader context, he sees oppression and domination of labor under capitalism system in advanced industrial society. He developed the critical theory as a way to educate public so that citizens transform their lives to the realization of freedom and social justice that are two important pillars of social democracy. Thus, democracy does not stop the political affair but rather a mass or social democracy of life imbued with the values of justice and freedom.